VIRTUAL LABORATORIES IN SCIENCE EDUCATION AT ISLAMIC ELEMENTARY SCHOOLS: A LITERATURE REVIEW - Rizka Febriyani Awliyah; Annajmi; Annisa Salva Putri; Melisa; Silvi Maharani; Tatik Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science education emphasizes the development of conceptual understanding, science process skills, and scientific attitudes through practical activities. However, the implementation of laboratory-based science learning in Madrasah Ibtidaiyah is often constrained by limited laboratory facilities, equipment, and instructional resources. Virtual Laboratories have emerged as an alternative learning environment that can address these limitations. This study aimed to examine the use of Virtual Laboratories in science education at Madrasah Ibtidaiyah through a literature review. The study reviewed national and international scholarly publications published between 2015 and 2025. Relevant literature was retrieved from Scopus, ERIC, and Google Scholar and analyzed using thematic content analysis. The findings indicate that Virtual Laboratories provide a flexible and interactive learning environment that supports practical science instruction. The synthesis identified three major educational benefits: improving students' conceptual understanding, strengthening science process skills, and increasing learning motivation. The review also suggests that Virtual Laboratories are compatible with the cognitive characteristics of elementary school students, although their implementation is influenced by the availability of digital infrastructure and teachers' technological and pedagogical competencies. Therefore, Virtual Laboratories should be regarded as complementary learning environments that enrich rather than replace conventional laboratory activities in science education.